2014
DOI: 10.1016/j.chemosphere.2014.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic meta-analysis of risk from the exposure to Hg in artisanal gold mining communities in Colombia

Abstract: HIGHLIGHTSo Data of Hg in air and in fish across Colombia are evaluated in terms of risk. o Probability distribution functions are fitted to exposure and concentration data. o lnhalation of Hg contributes more to the overall risk than ingestion of fish. o The risk for the residents of mining communities greatly exceeds the threshold of 1. o The risk for miner-smelters is 200 times higher than what is deemed acceptable. A B S T R A C TColombia is one of the largest per capita mercury polluters in the world as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 37 publications
(32 reference statements)
0
15
0
4
Order By: Relevance
“…2; Nevado et al, 2010;Swenson et al, 2011;Asner et al, 2013;De Miguel et al, 2014;Marinho et al, 2014). Although gold mining activities have existed in the Amazon for decades, they have recently surged following a 360% increase in gold prices after 2000 ( Fig.…”
Section: Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…2; Nevado et al, 2010;Swenson et al, 2011;Asner et al, 2013;De Miguel et al, 2014;Marinho et al, 2014). Although gold mining activities have existed in the Amazon for decades, they have recently surged following a 360% increase in gold prices after 2000 ( Fig.…”
Section: Miningmentioning
confidence: 99%
“…Although gold mining activities have existed in the Amazon for decades, they have recently surged following a 360% increase in gold prices after 2000 (Fig. 2;Nevado et al, 2010;Swenson et al, 2011;Asner et al, 2013;De Miguel et al, 2014;Marinho et al, 2014). Artisanal miners extract gold by dredging sediments from the river bottom and using mercury (Hg) to amalgamate fine gold particles, thereby altering stream and river morphology, increasing suspended sediment loads, and polluting waters via the release of Hg.…”
Section: Miningmentioning
confidence: 99%
“…A recent work by Alvarez (2013a) estimated a mean concentration of 1.36 mg/kg for mercury in bivalves from the Dagua river, which is a value almost three times higher than the standard legal limits of 0.5 mg/kg for fish products (Resolution 776/2008). Likewise, De Miguel et al (2014) indicated that mercury concentration in fish ranged from 0.026 to 3.3 mg/kg arising from artisanal gold mining in Colombia. The same authors further state that the mercury concentration in fish of Valle del Cauca ranged from 0.16 to 0.5 mg/kg.…”
Section: Statementioning
confidence: 99%
“…Mercury vapour impacts public health most directly, causing problems with the respiratory tract in short-term exposure to high levels of mercury vapour. Symptoms include chest pains, dyspnoea, cough, haemoptysis, impairment of pulmonary function and interstitial pneumonitis [11,18,19]. The mercury contamination in Colombia by artisanal gold mining has been recognized by a number of researchers and local authorities for over a decade.…”
Section: Introductionmentioning
confidence: 99%
“…During this operation, a large amount of Hg is accidentally or intentionally discharged to the environment and eventually reaches nearby fresh water bodies where, together with the significant amounts of mercury supplied by wet atmospheric deposition, it is subjected to methylation and subsequently bioaccumulation in aquatic fauna [16]. In order to recover the gold, the amalgam is heated in open charcoal furnaces either on site, or in small workshops (or even in the home of the miner) and the emitted Hg vapors are inhaled by the unprotected artisanal minersmelters, but also outdoors and at home by residents of the mining communities [17,18]. Mercury vapour impacts public health most directly, causing problems with the respiratory tract in short-term exposure to high levels of mercury vapour.…”
Section: Introductionmentioning
confidence: 99%